German universities as state-sponsored co-operatives - Alexander Dilger (Management Revue, 2007)
Most universities in Germany are public firms but they have many properties of cooperatives. The most important thereof are described and analysed together with the characteristics of state-sponsorship. The real companions of the university as a cooperation are its professors. The same is true for the faculty level, perhaps even more so. However, especially the students are also organised in a co-operative form as are the representatives of all membership groups together. The state is making some crucial reforms that transform this university model or may even destroy it. In any case, the change is slow, painful and open-ended.
Keywords: 650; co-operative; incentive; professor; reform; tenure; university